HUBUNGAN KARAKTERISTIK IBU DENGAN PENGGUNAAN KONTRASEPSI KB PIL DI KLINIK DAN RUMAH BERSALIN A PURWAKARTA TAHUN 2020 - Lia Yulianti; Armiyanti Armiyanti; Shanti Shanti (Jurnal Ilmiah Kesehatan, 2021)
Purpose: The aim of this study was to determine the characteristic relationship of age, parity, education and occupation with birth control pills at the Purwakarta Clinic and Maternity Hospital. Methods: This study uses quantitative methods with cross sectional design. The subject of study was fertile age women who became acceptors of birth control pills at Purwakarta Clinic A. The sample of this study is women of childbearing age taken with total sampling and as many as 57 people. Result: The results showed a significant relationship (pvalue <0.05) between maternal age and parity, with the contraceptive contraceptive pill at the Purwakarta Clinic and Maternity Hospital. While the unrelated factors are the mother's work and education with the contraception of birth control pills at the Purwakarta Clinic and Maternity Hospital.. Conclusion: A significant relationship between maternal age and parity, with the contraceptive contraceptive pill at the Purwakarta Clinic and Maternity Hospital. The unrelated factors are the mother's work and education with the contraception of birth control pills at the Purwakarta Clinic and Maternity Hospital